IMPLEMENTASI PENEGAKAN HUKUM BAGI PENGEDAR NARKOTIKA DI INDONESIA - Fathur Rachman (PRANATA HUKUM, 2017)
The circulation of narcotics is a big problem for Indonesia, so the need to discuss about the proper sanctions for narcotics dealers. then the subject matter in this paper about the legal sanctions for narcotics drug dealer in Indonesia. Problem approach using normative juridical approach (legal research). Narcotics dealer in a criminal act is an illegal narcotics dealer who is given a criminal sanction under Article 114 of Law Number 35 Year 2009 on Narcotics, with maximum threat of a sentence of 20 years or life imprisonment or death penalty or a fine. Law enforcers must be firm and eradicate the narcotic crime, Narcotics drug dealers should be given sanctions and deterrent effects for the perpetrators and gangs.